AB1124 PREDICTIVE VALUE OF MRI FOR CT-GUIDED POSITIVE BIOPSY IN SUSPECTED INFECTIOUS SPONDYLODISCITIS. (June 2019) - Tekaya, Aicha Ben; Ammar, Lobna Ben; Saidane, Olfa; Tekaya, Rawdha; Hammamia, Mohammed Ben; Mahmoud, Ines; Abdelmoula, Leila
Abstract : Background: Spondylodiscitis is a potentially life-threatening infection burdened by high morbidity rates. MRI remains the key examination in the diagnosis of infectious spondylodiscitis. The microbiological diagnosis is the main predictive factor for successful treatment. Objectives: To evaluate the MRI characteristics associated with the detection of microbial pathogens by computed tomography (CT) guided biopsy in case of suspicion of infectious spondylodiscitis. Methods: Retrospective study including all patients hospitalized in our department between 1999 and 2019 and who underwent MRI and CT-guided biopsy for suspicion of septic spondylodiscitis.The diagnosis was based on clinical, biological, radiological and bacteriological data. We divided the patients into two groups: patients with a non-contributory CT guided biopsy (group 1) and patients with a contributory biopsy (Group 2). Results: We included 82 patients including 37 women and 45 men with a mean age of 56 years old [16 - 86]. The median delay of consultation was 3 months. Inflammatory back pain was reported in 78% of cases. Neurologic deficiency was noticed in 19.5% of cases. The lumbar spine was involved more than 50% of cases. Spinal MRI was performed to all patients and showed paravertebral abscess in 64.6%, epiduritis in 62.1%, intra-discal abscess in 3.6%, spinal cord compression 10.9%, and vertebral ostelysis in 6.09% of cases.The causative microorganism was mycobacterium tuberculosis in 53.6%, brucella in 24.3%, and pyogenic germs in 15.8% of cases. Disco vertebral biopsy was performed in 55 patients and was contributory in 45.4% of cases. The presence of spinal cord compression, intra-discal abscess and vertebral osteolysis was more frequent in group 2, but with no statistically significant difference (p = 0.65, 1 and 0.58; respectively). In addition, there was no significant difference in the presence of paravertebral abscess and epiduritis (p = 0.41 and 0.53; respectively). Conclusion: Spondylodiscitis is an emergency which must be diagnosed on time to avoid life threatening complications, neurological sequelae and spinal deformities. Disclosure of Interests: None declared